Sistem Informasi Penerimaan Mahasiswa Baru - Kletus Beda (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The system is a series of two or more interconnected components, which interact to achieve a goal. Meanwhile, information is data that has been managed and processed to provide meaning and improve the decision-making process. According, information systems are systems that exist within an organization where the need for daily transaction processing that supports managerial organizational operations functions with strategic activities of an organization for the purpose of providing certain outside parties with the necessary reports. The new student registration information system is a routine activity carried out by the university in every new academic year. Computers have spread in various fields, both in the world of work and the world of education so that it has indirectly created very tight competition between one university and another. The new student registration information system at the University of Flores was designed and built using the PHP programming language and MySQL database. To test the quality of this system the author uses black box testing / black box testing. The black box testing method is one method that focuses on software testing. The new student registration information system at the University of Flores is expected to facilitate officers in processing prospective student data so that the new student registration process becomes more effective and efficient. Keywords: New Student Admission, Waterfall, Website, PHP, MySQL, Black Box Testing